The Beauty and the Beast of Earning Management in Indonesia - Mertha Jaya, I Made Laut; Narsa, I Made (Opción, 1970)
Earnings management is controversial for the business and accounting worlds. Whether an action is accessed to be proper or not can only be done by certain individuals based on the level of understanding they have. This research prioritized the concept of understanding of earnings management patterns carried out by companies in Indonesia for eleven years (2008-2018). This research was conducted using a descriptive quantitative method with 1,023 data analysis of 93 selected company samples from a total of 676 companies on the Indonesia Stock Exchange. This study concludes that three types of ratio scales can be used in interpreting a pattern of earnings management in all companies in Indonesia, as measured by discretionary accruals.